2013
DOI: 10.5014/ajot.2013.008110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a 10-Week Tier-1 Response to Intervention Program in Improving Fine Motor and Visual–Motor Skills in General Education Kindergarten Students

Abstract: This study provides preliminary evidence that a Tier 1 RtI program can improve fine motor and visual-motor skills in kindergarten students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 21 publications
5
56
1
1
Order By: Relevance
“…Only two studies (Axford et al, ; Ohl et al, ) evaluated interventions designed to develop fine motor control (see Table ). These sampled typically developing children aged 5–6 years, implemented interventions of approximately equal duration (9–10 weeks), but differed in implementation strategy (teacher‐led technology vs. multidisciplinary team) and intensity (150 vs. 30 min).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only two studies (Axford et al, ; Ohl et al, ) evaluated interventions designed to develop fine motor control (see Table ). These sampled typically developing children aged 5–6 years, implemented interventions of approximately equal duration (9–10 weeks), but differed in implementation strategy (teacher‐led technology vs. multidisciplinary team) and intensity (150 vs. 30 min).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of outcomes were used across the studies (describable as measuring VMI, manual dexterity, and handwriting; as defined in Table ), with inconsistent results. Ohl et al () found significant improvement at post‐test for VMI and manual dexterity (measured by the Bruininks–Osteresky Test of Motor Proficiency 2nd Edition) but not for pen grip, whereas Axford et al () report no benefits to VMI but improvements in drawing (motor coordination subtest of the Beery–Buktenica Developmental Test of Visual‐Motor Integration). Axford et al () also implemented the Shore Handwriting Screen (Shore, ), with only one of its five outcomes (copying capital letters) significantly improving following intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Handwriting skills are the result of a multiplex integration of sensorimotor, cognitive, perceptual, visual and sensory systems that work together to accomplish a successful writing task (Hoy, Egan, & Feder, ; Lust & Donica, ; Mackay, McCluskey, & Mayes, ; Pfeiffer, Rai, Murray, & Brusilovskiy, ; Van Drempt, McCluskey, & Lannin, ). Early developmental stages in both preschool‐age and elementary school‐age children build the foundation for higher order processes required later in life, especially when students need to make longer sentences and produce complex compositions (Bazyk et al, ; Engel‐Yeger, Nagauker‐Yanuv, & Rosenblum, ; Lust & Donica, ; Ohl et al, ; Pfeiffer et al, ; Thompson, Mclaughlin, Derby, & Conley, ; Van Hartingsveldt, Groot, Aarts, & Nijhuis‐Van Der Sanden, ).…”
Section: Introductionmentioning
confidence: 99%